2021
DOI: 10.1021/acsearthspacechem.1c00084
|View full text |Cite
|
Sign up to set email alerts
|

Orthocarbonates of Ca, Sr, and Ba—The Appearance of sp3-Hybridized Carbon at a Low Pressure of 5 GPa and Dynamic Stability at Ambient Pressure

Abstract: Orthocarbonates are a newly discovered class of compounds that are stable at high pressures. The presence of sp3-hybridized carbon, having structural similarity to orthosilicates, and their potential participation in the global planetary carbon cycle have triggered intensive theoretical and experimental investigations into these compounds. Here, based on the density functional theory and crystal structure prediction calculations, we predict new stable crystal structures of the orthocarbonates Sr3CO5-Cmcm, Sr3C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

6
43
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 24 publications
(51 citation statements)
references
References 54 publications
6
43
2
Order By: Relevance
“…The anisotropic displacement parameters of the symmetrically independent strontium as well as of the oxygen atoms were constrained to be identical. 25 We suggest that this reaction occurs in our experiments during the second stage of heating.…”
mentioning
confidence: 63%
See 4 more Smart Citations
“…The anisotropic displacement parameters of the symmetrically independent strontium as well as of the oxygen atoms were constrained to be identical. 25 We suggest that this reaction occurs in our experiments during the second stage of heating.…”
mentioning
confidence: 63%
“…28 In addition to the established orthoanions, it was recently predicted and experimentally shown that carbonates with [CO 4 ] 4− groups may even be recovered at ambient conditions. 21,25 Further, stable structures with stoichiometries M 2 [CO 4 ] and M 3 [CO 4 ]O (M = Mg, Ca, Sr, and Ba) have been predicted by DFT-based calculations. 22−25 Here, we report the successful outcome of the synthesis of one of these structures using M = Sr.…”
mentioning
confidence: 99%
See 3 more Smart Citations